Fluoxetine and nortriptyline affect NTPDase and 5'-nucleotidase activities in rat blood serum - Eduardo Luiz Pedrazza (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-09-06T12:49:03Z No. of bitstreams: 2 Fluoxetine_and_nortriptyline_affect_NTPDase_and_5nucleotidase_activities_in_rat_blood_serum.pdf: 286438 bytes, checksum: f33446ca78e15224ca4c0671dd96e051 (MD5) Fluoxetine_and_nortriptyline_affect_NTPDase_and_5nucleotidase_activities_in_rat_blood_serum.pdf: 286438 bytes, checksum: f33446ca78e15224ca4c0671dd96e051 (MD5)